Predicting future performance and dividend policy by asset revaluation and leverage - Ridwan Ridwan; Yossi Diantimala; Indayani Indayani (Jurnal Keuangan dan Perbankan, 2022)
This study aims to examine the effect of asset revaluation on the company's future performance and dividend policy through leverage as a mediating variable. Financial statements play an important role as a source of information for stakeholders in predicting the company's future performance. Stakeholder interest in dividends is limited by biased information about the company's future performance through leverage levels and asset revaluation results that can be handled through financial statements in decision making for dividend distribution. Therefore, this study supports agency theory and dividend policy theory. The sample of this research is 205 financial statements of companies listed on the Indonesia Stock Exchange for the period 2012-2019. The analytical method used is Path Analysis. The results show that an increase in asset revaluation reduces the company's level of leverage and future company performance, and an increase in the benefits of asset revaluation increases the company's dividend policy. The increase in leverage has a positive contribution to the company's performance in the future but does not have a significant effect on dividend policy due to the high level of company debt. Meanwhile, leverage does not mediate an increase in asset revaluation on future company performance and dividend policy. This study contributes to the improvement of the model to predict the company's future performance by implementing business strategies on asset revaluation and leverage.